PERAN PROFITABILITAS DALAM MEMODERASI HUBUNGAN ANTARA STRUKTUR MODAL, NON PERFORMING LOAN (NPL) DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - Qur’ani, Ribby Mufidah; Pramitasari, Triska Dewi; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2025)
Banking companies listed on the Indonesia Stock Exchange represent a strategic sector that significantly contributes to the national financial system and economic stability. This study aims to analyze the effects of capital structure, Non-Performing Loans (NPL), and firm size on firm value, as well as to examine the moderating role of profitability in these relationships among banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The population of this study consists of 47 banking companies, from which 9 companies selected as samples using a purposive sampling method. The data analysis technique employed is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the study reveal that capital structure and firm size have a significant effect on firm value, while non-performing loans (NPL) do not exhibit a significant effect. Furthermore, profitability is shown to moderate the relationship between capital structure and firm size with firm value, but does not moderate the relationship between NPL and firm value. These findings imply that improving profitability can enhance firm value by optimizing capital structure and expanding the scale of corporate assets.